Triple-Entry Bookkeeping and Income Momentum (Book). - Meyer, Philip E.; Shank, John K. (The Accounting Review, 1983)
Abstract Reviews the book "Triple-Entry Bookkeeping and Income Momentum," by Yuji Ijiri.